Effectiveness of A New Visual Distraction Technique in Decreasing Kinesiophobia with Chronic Neck Pain. - Devi, Poorva; Bhole, Diptee (Indian Journal of Physiotherapy & Occupational Therapy)
Background: Kinesiophobia or fear of movement is a cause of decreased level of activity in patients with chronic neck pain. Traditional forms of treatment, such as physiotherapy alone, can tackle problems of neck pain, but not kinesiophobia. This study aims to study the effect of visual distractiontechnique in the treatment of kinesiophobia. Study design: Quasi experimental study. Methods: A total of 43 participants with chronic neck pain and kinesiophobia were selected for the study. These participants underwent assessments on the NRS, Tampa scale and evaluation of cervical ROM. Assessment was done pre and post intervention of two weeks. Results: A significant reduction in Tampa score and NRS scores was observed and improvement in cervical ROM were seen post intervention in all subjects. Conclusion: The new visual distraction tool is effective in reducing kinesiophobia levels and NRS scores and improving cervical ROM in patients with chronic neck pain with kinesiophobia.